The physiological linkage between molar inclination and dental macrowear pattern. Issue 4 (6th April 2018) - Oxilia, Gregorio; Bortolini, Eugenio; Martini, Sergio; Papini, Andrea; Boggioni, Marco; Buti, Laura; Figus, Carla; Sorrentino, Rita; Townsend, Grant; Kaidonis, John; Fiorenza, Luca; Cristiani, Emanuela; et al.
Abstract: Objectives: Exact symmetry and perfect balance between opposite jaw halves, as well as between antagonistic teeth, is not frequently observed in natural masticatory systems. Research results show that asymmetry in our body, skull, and jaws is often related to genetic, epigenetic, environmental and individual ontogenetic factors. Our study aims to provide evidence for a significant link between masticatory asymmetry and occlusal contact between antagonist teeth by testing the hypothesis that tooth inclination is one of the mechanisms driving distribution of wear in masticatory phases in addition to dietary and cultural habits. Materials and Methods: The present work investigates the relationship between dental macrowear patterns and tooth inclinations on a sample of complete maxillary and mandibular 3D models of dental arches from 19 young and adult Yuendumu Aboriginal individuals. The analysis was carried out on first molars (M1) from all quadrants. Occlusal Fingerprint Analysis was used for the quantification of macrowear patterns, and 2D cross‐sectional geometric analysis was carried out to investigate asymmetry in dental arches. Results: The asymmetry is highly variable on both arches, and it is associated with differences in the inclination of upper M1 crowns. Each molar has variable inclination (buccal/lingual) which influence tooth to tooth contact, producing greater or lesser variation in wear pattern. Interindividual variability of morphological variation of the occlusal relationship has to be considered in macrowear analysis. Discussion: Our results suggest that overall asymmetry in the masticatory apparatus in modern humans affects occlusal contact areas between antagonist teeth influencing macrowear and chewing efficiency during ontogeny.